1982
DOI: 10.1152/jappl.1982.53.6.1496
|View full text |Cite
|
Sign up to set email alerts
|

A Starling resistor regulates cerebral venous outflow in dogs

Abstract: This investigation was undertaken to determine whether a Starling resistor or venous waterfall effect exists between the sagittal sinus and the cerebral veins such that increases in sagittal sinus pressure (Pss) do not abolish cerebral venous outflow and to examine two possible contributions of extracranial venous valves in regulating outflow. Anesthetized dogs were subjected to positive end-expiratory pressure (PEEP) before and after intracranial pressure (Pic) was elevated by inflation of an epidural balloon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
81
0

Year Published

1986
1986
2016
2016

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 102 publications
(84 citation statements)
references
References 0 publications
3
81
0
Order By: Relevance
“…It has been demonstrated that the cerebral venous pressure (CVP) increases in parallel with the CSFP and it is always kept slightly higher than the CSFP. Parallel modifications in CSFP and CVP can be induced by the inflation of intracranial balloons or by the modification of the PaCO2 (Yada et al, 1973;Luce et al, 1982;Wiig and Reed, 1983). Thus, the increase in the CVP of the vessels draining the tumour could lead to a further increase in the tumour MVP and IFP.…”
Section: Discussionmentioning
confidence: 99%
“…It has been demonstrated that the cerebral venous pressure (CVP) increases in parallel with the CSFP and it is always kept slightly higher than the CSFP. Parallel modifications in CSFP and CVP can be induced by the inflation of intracranial balloons or by the modification of the PaCO2 (Yada et al, 1973;Luce et al, 1982;Wiig and Reed, 1983). Thus, the increase in the CVP of the vessels draining the tumour could lead to a further increase in the tumour MVP and IFP.…”
Section: Discussionmentioning
confidence: 99%
“…2 When calculating the CPP, the mean arterial pressure (MAP) is commonly used as effective upstream pressure and the intracranial pressure (ICP) as effective downstream pressure (EDP) of the cerebral circulation, because of a Starling resistor phenomenon located at the level of cerebral veins. 3 However, another major component of the EDP is the critical closing pressure (CCP), which cannot be directly measured in patients with spontaneous circulation. It has been proven that in vivo pressure-flow relationships are linear for many vascular beds, including the cerebral vessels.…”
Section: Introductionmentioning
confidence: 99%
“…2. The existence of a subdural venous collapse was demonstrated already in 1928 (26), but its physiological role or its role in various pathophysiological conditions for brain circulation has not until recently received any scientific attention (20,27,28).…”
Section: General Physiological and Physical Principlesmentioning
confidence: 99%